An Empirical Investigation into The Effect of Poverty and Inflation on Health Outcomes in West Africa - Abere Benjamin Olusola (INTERNATIONAL JOURNAL OF ECONOMICS AND FINANCIAL MANAGEMENT, 2026)
This study examined the impact of poverty and inflation on health outcomes in West Africa, with emphasis on understanding how dropping income levels and continuous price instability influence healthcare access, usage, and general population well-being. The aims were to evaluate the extent to which per capita income (PCI) and consumer price index (CPI) affect health indicators, while also analysing the complementary effects of literacy rate (LTR) and public health expenditure (PHE). The research conducted panel data analysis covering different West African countries over a 30-year period (1990–2020). Fixed effects, random effects, and Hausman specification tests were conducted, alongside diagnostic checks for cross-sectional dependence and model stability. The robustness of findings was assured utilising alternative estimating strategies. The study focusses on selected West African countries, offering a regional perspective on the socioeconomic and macroeconomic factors of health outcomes. Variables investigated included PCI (poverty proxy), CPI (inflation measure), LTR (education), and PHE (public health investment). Results demonstrated that poverty, assessed through low PCI, significantly impairs health outcomes, whereas inflation (CPI) exerts a negative influence by reducing real income and access to healthcare. Conversely, literacy rate (LTR) and public health expenditure (PHE) revealed positive and significant consequences, showing the critical importance of education and government investment in improving health conditions. The research advocates comprehensive poverty reduction programs, stronger inflation-targeting frameworks, and extension of social safety nets to safeguard vulnerable people. Furthermore, scaling up education and public health investment is vital for improving long-term health outcomes. Regional engagement among West African countries is also encouraged to promote economic stability and health sector resilience.